Extraction of Gluconic Acid by Complex Formation with Alamine 336 - Inci, Ismail (Asian Journal of Chemistry, 2010)
The purpose of this study is to present novel distribution data for gluconic acid between water and different organic solutions of Alamine 336. Extraction equilibria of gluconic acid in the system solution of Alamine 336 in mixtures of 5 various solvents at 298.15 K have been measured. The solvents used in this study are hexane, cyclohexane, toluene, methyl isobutyl ketone (MIBK) and propanol. Using Bizek approach two acid : amine complexes, (Acid)·(Amine) and (Acid)·(Amine)2 are assumed to exist in the organic phase in the case of proton-donating diluents, while the complexes (Acid)·(Amine) and (Acid)2·(Amine)3 are suggested in the case of non-proton-donating diluents. As a result of batch extraction experiments distribution coefficients (D), loading factors (Z) and overall extraction constants (K11, K12, K23) are calculated.